Comparison of the prognosis value of CTP - crea, traditional CTP , MELD in cirrhotic patients with acute variceal bleeding - Phan, Trung Nam; Nguyen, Van Loc (Tạp chí Y Dược Huế, 2022)
Background: Variceal bleeding is a severe complicaton of portal hypertension due to cirrhosis with high rate of motality. The aims of this study was to compare the accuracy of CTP - crea (creatinine-modified Child Turcotte Pugh score) with traditional CTP and MELD score for predicting in rebleeding and mortality within first five days and 6-week in cirrhotic patients with acute variceal bleeding. Methods: Prospective study in 118 cirrhotic patients presenting with acute variceal bleeding were hospitalized and diagnosed by upper GI endoscopy submited to calculate CTP-, CTP - crea I/II- and MELD- score. Exclusion criteria were patients with chronic kidney diseases, hepatocellular carcinoma, severe primary cardiopulmonary failure. Results: The mean age of patients was 53.39 ± 11.97 years, male accounted for 91.0%. The patients with bleeding from esophageal varices were accounted for 82.2% and from gastric varices for 17.8% of which GOV2, IGV1, GOV1 were 11.9%, 3.4%, 2.5%, respectively. Acute kidney injury (AKI) was presented in 16.7% of patients. The prognostic value of these scores in early rebleeding (first five days) were: CTP - crea I (AUC: 0.788) > CTP - crea II (AUC: 0.771) > MELD (AUC: 0.754) > CTP (AUC: 0.671), in early mortality were: CTP crea I (AUC: 0.860) > CTP - crea II (AUC: 0.859) > MELD (AUC: 0.849) > CTP (AUC: 0.775). For the 6-week rebleeding, only the CTP - crea I score has prognostic value with AUC = 0.67 (p < 0.05), while the 6-week mortality, the prognostic value of CTP - crea I was the best score (AUC: 0.818) > CTP - crea II (AUC: 0.804) > MELD (AUC: 0.772) > CTP (AUC: 0.745). Conclusions: The CTP - creatinine scores improved the traditional CTP score and was better than the MELD score in predicting the rebleeding and mortality outcomes in patients with acute variceal bleeding. It is possible to routinely apply this score in clinical practice to stratify and predict the outcomes in variceal bleeding cirrhotic patients in Vietnam.